Determinan Opini Audit Going Concern Perusahaan Yang Terdaftar Pada JII 2019-2021 - Elvida Anggi Fauziyah; Dianita Meirini (Fakultas Ekonomi Universitas Kadiri, 2023)
The aim of study was to determine the effect of the determinants of the going concern audit opinion consisting of return on assets, current ratio and sales growth at companies listed in JII for the 2019-2021 period, the type of research was descriptive quantitative. The data analysis technique used logistic regression. partial return on assets, current ratio and sales growth have no effect on going concern audit opinion, while simultaneously return on assets, current ratio and sales growth affect going concern audit opinion by 92%